Deep-sea cage culture altered microbial community composition in the sediments of the Yellow Sea Cold Water Mass. (October 2022) - Li, Shuting; Li, Li; Gao, Qinfeng; Dong, Shuanglin; Shi, Shuai
Abstract: Environmental impacts of the first submersible salmonid culture cage, which was launched in the deep-sea of the Yellow Sea Cold Water Mass, were investigated. The temporal and spatial variations of several physicochemical parameters were observed in both the bottom and sediment pore water. Aquaculture activities decreased bacterial richness in the sediment. The dominant phyla Proteobacteria, Desulfobacterota and Acidobacteriota, accounted for 30.42 % of the total bacteria community. Principal component analysis indicated that the bacterial composition in December was different from that in the other three months, and the aquaculture activity affected the distribution of the sediment microbial community in June, August and April. Planctomycetes was selected as biomarkers in the aquaculture area by linear discriminant analysis effect size. Redundancy analysis showed that the biomarkers were positively correlated with temperature and the concentration of nitrite in June, and negatively correlated with the dissolved oxygen in August and April. Graphical abstract: Unlabelled Image Highlights: We first investigated the impact of the aquaculture activities on the YSCWM. Spatial and temporal variations of the microbial community were observed. Different biomarkers were selected by LEfSe in different sampling times and sites. Variations of microbial structure were correlated with physicochemical parameters.